2018
DOI: 10.1007/s40520-018-0950-9
|View full text |Cite
|
Sign up to set email alerts
|

Falls in Mexican older adults aged 60 years and older

Abstract: Background Falls are a major cause of disability, morbidity, institutionalization, and mortality in older adults. Objectives To examine the risk factors for falls among Mexican older adults aged 60 years and older. Methods This study included 6,247 participants and their spouse or partner aged 60 years and older from the Mexican Health and Aging Study, an ongoing longitudinal study (2001-2012) conducted in Mexico. Measures included socio-demographics, falls, physical activity, comorbid conditions, pain, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
(35 reference statements)
5
18
0
9
Order By: Relevance
“…In our study, low ADL scores and low mobility were associated with high risk of falling. Similar results have been previously reported [28,29]. These results show that facilitating the maintenance of healthy ADLs in older adults is necessary, but some mobility behaviors may be associated with the risk of falling [30].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, low ADL scores and low mobility were associated with high risk of falling. Similar results have been previously reported [28,29]. These results show that facilitating the maintenance of healthy ADLs in older adults is necessary, but some mobility behaviors may be associated with the risk of falling [30].…”
Section: Discussionsupporting
confidence: 90%
“…Urinary incontinence is more common in females than in males. Prevalence increases with age [24][25][26]. In our study, it was seen that the majority of all patients (75.2%) were at or above forty-five years of age.…”
Section: Discussionsupporting
confidence: 50%
“…Not surprisingly, we recorded more falls among women compared to men. Most cross-sectional and longitudinal studies in community-dwelling older people have revealed a higher ratio of falls in older women [24][25][26][28][29][30][31]. Decreased muscle strength, increased visual field dependence and variation in gait pattern during dual-task activities in older women have been suggested to be among the causes of higher risk of falls [32,33].…”
Section: Discussionmentioning
confidence: 99%